The Possibilities of Working Capacity Maintenance at Organophosphorous Compounds Intoxication - A. Yu. Mikshta; L. P. Erdniev; A. A. Vlasov; I. V. Legotin; I. A. Ermolaeva; S. A. Komissarenko; I. A. Nelga (Вестник войск РХБ защиты, 2023)
The experience of modern local armed conflicts and the monitoring of terrorist activity in the world indicate the possibility of the affection of people by organophosphorus compounds (OPs) in combat and as a result of industrial accidents and terrorist acts. It can be predicted that in case of timely use of PPE by the personnel, in addition to lethal and severe affections, up to 30 ± 5% of them will be mild forms of intoxication. It is shown in the article, that the actoprotectors with different mechanism of action (hypoxene, octodrine and meldonium) increase the endurance of experimental animals with mild poisoning of OPs in case of single oral administration. Moreover, the degree of inhibition of peripheral blood acetylcholinesterase of all animals treated with model OPs did not differ between groups and ranged from 8 to 24%. As a result of the experiments on animals, the preparations were distributed in the following order: meldonium <octodrine <hypoxene. Joint oral administration of the test substances was not accompanied by a potentiation of the actoprotective effect. It is established, that the combined use of the studied actoprotectors is comparable with the isolated administration of meldonium, has no advantages over the use of octodrine and surpasses hypoxene in rate of onset of the effect, but is inferior to it in severity and duration. These facts indicate the viability of use of the studied actoprotectors to prevent a decrease in combat readiness in case of the threat of the affection by OPs (hypoxene), for its urgent increase in case of mild affection (octodrine) and for the complex treatment of poisoning due to organophosphates (OPs) (meldonium, hypoxene).